2004
DOI: 10.1021/jp031267y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Activity of Nitrogen-Doped Rutile TiO2(110) in Visible Light

Abstract: TiO2(110) single crystals, doped with nitrogen via an NH3 treatment at 870 K, have been found to exhibit photoactivity at photon energies down to 2.4 eV, which is 0.6 eV below the band-gap energy for rutile TiO2. The active dopant state of the interstitial nitrogen that is responsible for this effect exhibits an N (1s) binding energy of 399.6 eV and is due to a form of nitrogen that is probably bound to hydrogen, which differs from the substitutional nitride state with an N (1s) binding energy of 396.7 eV. Opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
561
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(616 citation statements)
references
References 29 publications
36
561
0
Order By: Relevance
“…Highly-transparent and highly-ordered TiO 2 mesoporous multilayer thin films with variable thicknesses were fabricated via 30 an evaporation induced self-assembly method. The conversion efficiency of the highly-ordered TiO 2 thin film solar cells (0.82%) was 5 times superior to that of the transparent Solaronix photoanode solar cells (0.16%), with photoanodes of a similar thickness (approximately 1 µm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly-transparent and highly-ordered TiO 2 mesoporous multilayer thin films with variable thicknesses were fabricated via 30 an evaporation induced self-assembly method. The conversion efficiency of the highly-ordered TiO 2 thin film solar cells (0.82%) was 5 times superior to that of the transparent Solaronix photoanode solar cells (0.16%), with photoanodes of a similar thickness (approximately 1 µm).…”
Section: Discussionmentioning
confidence: 99%
“…28 This result has been accepted by other researchers. [29][30] As for the peak at 398 27 However, Zhou et al suggested that the 398 eV peak should be attributed to the invasion of N atoms into the interstitial sites of the TiO 2 crystal lattice , expressed as the Ti-N-O bond, and this conclusion was confirmed by a 55 temperature programmed desorption (TPD) experiment. 31 In our study, the absence of any peak around 400 eV in the N 1s spectrum implies that there were no adsorbed nitrogen molecules in our samples.…”
Section: Performance Of Solar Cells With N-doped Mesoporous Tio 2 Phomentioning
confidence: 97%
See 1 more Smart Citation
“…This assignment can also be proved by the previous literature. 2,3 The BE of N 1s is even lower than that of titanium nitride, suggesting more charge transfer to the N ions and further oxidizing the Ti ions ͑e.g., from Ti 3+ to Ti 4+ ͒. This will break the charge balance in the TiO 2 system.…”
mentioning
confidence: 99%
“…The band gap is about 2.21 eV at highly symmetric G point, which is less than the experimental value of 3.0 eV. 19 The underestimated band gap can be due to the choice of exchange-correlation energy. The valence band mainly consists of the 2p, 2s states of O and 3d states of Ti.…”
mentioning
confidence: 81%